Infections among pediatric transplant candidates: an approach to decision-making - L'Huillier, Arnaud; Höcker, Britta (Pediatric transplantation, 2019)
Introduction The presence of infections in the immediate pretransplant period poses challenges in decision-making. Delaying transplantation because of these infections may be required, but is associated with a risk to the potential recipient. The aim of this project was to develop a structured framework based on expert opinion to guide decision-making regarding the safety of transplantation for candidates with infection immediately before transplant, and to show how this framework can be applied to clinical scenarios. Methods Categories were created as follows: Category A: no delay; Category B: brief delay (≤1 week); Category C: intermediate delay (>1 week); and Category D: more prolonged or indefinite delay. A survey containing 59 clinical scenarios was sent to members of the IPTA ID CARE committee. Answers were reviewed, and the level of agreement was characterized as follows: Level 1: ≥75% agreement; Level 2:51%-74% agreement; and Level 3: ≤50% agreement. 95% CIs were calculated for the mean overall agreement across 59 scenarios. Results Among the panel, the agreement level ranged from 33% to 92% with the mean overall agreement across the 59 scenarios being 61%. For 7/59 scenarios, the lower bound of 95% CI was greater than 50%, indicating a difference at the 5% level of significance between the observed proportion and the chance level of 0.5. Summary The document provides expert opinion regarding the need to delay transplantation in the setting of different infections. The most important points in the decision to proceed to SOT included the urgency of transplantation and the severity of infection.